Antibody inhibiting enzymatic activity of tumour-associated carbonic anhydrase isoform IX. - Murri-Plesko, M; Hulikova, A; Oosterwijk, E; Scott, A; Zortea, A; Harris, A; Ritter, G; Old, L; Bauer, S; Swietach, P; Renner, C (2011)
Carbonic anhydrase IX (CAIX) is a hypoxia-induced, membrane-tethered enzyme that is highly expressed in many cancers. It catalyses the hydration of CO(2) to HCO(3)(-) and H(+), and the reverse dehydration reaction. Recent studies have shown an important role for CAIX in pH regulation and it has been speculated that CAIX may play a role in supporting cancer progression towards more aggressive forms of the disease. Clinical correlative studies in many tumours have shown that high expression is related to poor outcome. In the present study, we have selected antigen-binding antibody fragments (Fab) against human CAIX by phage-display, and tested these for inhibitory potency on CAIX catalytic activity. Inhibition was assessed from the kinetics of the CAIX-catalysed reaction, using assays performed on intact cells over-expressing CAIX, and their CAIX-containing membrane fragments. Inhibition was also assessed in multi-cellular tissue-models (spheroids) from the kinetics of CO(2) venting. We have identified a Fab antibody, labelled MSC8, and its corresponding full-length IgG that inhibited CAIX by up to 57% and 76%, respectively, with half-maximal inhibition at 0.3μg/ml. Incubation of CAIX-expressing cells with MSC8 IgG produced a lasting inhibitory effect. The inhibitory effect was prompt and was also observed in isolated membrane-fragments, suggesting that a direct inhibitory interaction takes place between the antibody and CAIX. The inhibitory effects in spheroids argue for a physiological relevance of the antibody. Biologically-active antibodies against CAIX can be used as selective, high-affinity inhibitors in experimental studies to dissect the role of CAIX and, possibly, therapeutically by targeting a catalytically-active cancer-related protein.